Peran Video Pembelajaran Dalam Pengembangan Kemampuan Berpikir Kritis Siswa Dalam Pembelajaran IPA - Insanul Arif; Elfia Sukma (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
Science learning not only aims to improve conceptual mastery but also to develop students' critical thinking skills. One medium that can be used to support this goal is instructional videos. This article aims to examine the role of instructional videos in developing students' critical thinking skills in science learning. The method used is a literature study, analyzing various sources, including journals, books, and scientific articles relevant to the use of instructional videos and critical thinking skills. The results of the study indicate that instructional videos can increase student engagement in the learning process, help students understand abstract science concepts, and encourage students to observe, analyze, ask questions, and draw conclusions based on the information obtained. Furthermore, the use of instructional videos can create a more engaging and contextual learning experience, enabling students to actively explore the material. Thus, instructional videos play a crucial role as a learning medium that can support the development of students' critical thinking skills in science learning. Therefore, teachers need to utilize instructional videos appropriately and integrate them with learning activities that encourage students to think critically.